Spatial Distribution Patterns of Urban Growth, Dasymetric Mapping, and Air Pollution Standard Index (ISPU) in Bogor Regency (2018-2023) - Ramadhan, Alfarisi; Hermawan, Erwin; Hudjimartsu, Sahid Agustian (Journal of Applied Informatics and Computing, 2025)
Bogor Regency has undergone rapid industrialization and urban growth, raising concerns about deteriorating air quality and its health impacts. This study aims to analyze the spatial distribution of urban expansion and its relationship with air pollution levels between 2018 and 2023. Using Sentinel-5P and Sentinel-2A satellite imagery processed via Google Earth Engine (GEE), the research maps changes in land use and monitors key pollutants such as nitrogen dioxide (NO₂) and sulfur dioxide (SO₂). The Air Pollution Standard Index (ISPU) is used to classify air quality conditions. The results indicate a notable increase (16%) in urban areas, with population density rising from 178 to 180 inhabitants per hectare, and a shift toward higher pollution categories, with significant portions of the region now classified as "Unhealthy" increased from 17% in 2018 to 31% in 2023. The urban growth model demonstrated high accuracy (92.5%) and strong alignment with local monitoring data. Model evaluation showed a Mean Absolute Error (MAE) of 1.295 µg/m³ and Root Mean Square Error (RMSE) of 1.478 µg/m³, demonstrating strong agreement between predicted and observed data from the Bogor Regency Environmental Agency. These findings highlight the need for integrated urban planning and effective air quality management to reduce future health risks in Bogor Regency.